Trademark Protection, Absolute and Relative Grounds for Refusal of Trademark - Emruli, Safet; Agim Nuhiu; Besa Kadriu (European Journal of Multidisciplinary Studies, 2016)
A trademark is a sign that individualizes the goods of a given enterprise and distinguishes them from the goods of its competitors. Trademark may consist letters, words, slogans, symbols, numerals, pictures, name, logo, even sounds and smell. They are based on registration. One registered trademark gives to his owner the right to exclude others from using an identical or similar mark to identify its goods or service on market. Trademark owners should apply for registration by filling an application in national level, in their national office for protecting trademark rights which trademark will be protected only in that current country and in international level by filling one application where his trademark will be protected in many country depending in which country he has mark the protection. The law does not recognize every possible mark or symbol as a valid trademark, there are some criteria that one sign or mark have to satisfy to gain the trademark protection. Any sing which is not able to distinguish the goods and services can not be registered, and this is one of the reasons for rejection of registration. Sign or mark must be a “trademark”, must not fail on the absolute and relative grounds. Sign can be refusal for absolute ground if is not able to distinguish the goods and services. Unprotected mark will be consider also mark in conflicts with a prior right in another trademark or other distinctive sign will also be refusal, in this case for relative ground. Accordantly to this, the owner, during creating his mark should be original, natural, creative etc.
Keywords: trademarks, protection of trademark, absolute ground for refusal, relative ground for refusal.